2011
DOI: 10.1080/03081060.2011.577151
|View full text |Cite
|
Sign up to set email alerts
|

The periodic service intention as a conceptual framework for generating timetables with partial periodicity

Abstract: Many railway companies in Europe operate periodic timetables. Yet most timetables are not entirely periodic but have a mixture of different periodicities and many exceptions to cope with changing demand. Current approaches for automatic timetable generation are not able to deal with such partially periodic structures but consider only fully periodic inputs. We therefore introduce the periodic Service Intention (pSI) as a framework where customer-relevant information about train services can be described, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…On the other hand, it is also easy to transform periodic to non-periodic timetables using the unfolding technique, where the dependency between events in different periods is still reserved (Goverde, 2007;van der Meer, 2008). Additionally, partially periodic and non-periodic train services are also being adopted in practical train operations in Europe and China to cope with the non-uniformly distributed demand and exceptional situations, where the non-periodic expression would be applicable (Caimi et al, 2011;Forsgren et al, 2011;Wong et al, 2008;Canca et al, 2014;Cacchiani et al, 2014).…”
Section: Max-plus System For a Railway Networkmentioning
confidence: 98%
“…On the other hand, it is also easy to transform periodic to non-periodic timetables using the unfolding technique, where the dependency between events in different periods is still reserved (Goverde, 2007;van der Meer, 2008). Additionally, partially periodic and non-periodic train services are also being adopted in practical train operations in Europe and China to cope with the non-uniformly distributed demand and exceptional situations, where the non-periodic expression would be applicable (Caimi et al, 2011;Forsgren et al, 2011;Wong et al, 2008;Canca et al, 2014;Cacchiani et al, 2014).…”
Section: Max-plus System For a Railway Networkmentioning
confidence: 98%
“…In (c) a periodic timetable is generated and in (d) it is rolled out to a complete day T should therefore be chosen to reduce the problem size as much as possible without violating the equivalence condition. The equivalence always holds for T > 2W , where W is the size of the largest time slot (see Caimi et al 2011c for details).…”
Section: Projection-based Solution Approachmentioning
confidence: 98%
“…minimising total travel time) in the projection will be rolled out to an optimal original solution if the equivalence is guaranteed. It can be shown that the equivalence depends on the length T of the time period on which the problem is projected: the smaller the period length, the more probable the violation of the equivalence (Caimi et al 2011c). The value of Fig.…”
Section: Projection-based Solution Approachmentioning
confidence: 98%
See 1 more Smart Citation
“…We remark that lines together with a rough time frame have been also denoted as (periodic) service intensions (see Caimi et al 2009) as the line concept contains the customer-relevant information about the public transport system.…”
mentioning
confidence: 99%